Peer Exclusion: a Social Convention or Moral Decision? Cross-Cultural Insights into Students’ Social Reasoning - Ha, Seung Yon (Journal of cognition and culture, 2020)
In this study, we examined the role of culture on early adolescents’ social reasoning about peer exclusion. A total of 80 U.S. and 149 Taiwanese early adolescents (U.S.: Mage = 11.00, SDage = 0.48; Taiwan: Mage = 10.45, SDage = 0.39) independently completed a social reasoning essay about peer exclusion. Analyses of the essays based on social-moral theories showed that U.S. students tended to reason about peer exclusion based on social conventional thinking whereas Taiwanese students were more attentive to personal and moral issues. Despite this difference, both groups of students referred to some common social-moral concepts while reasoning about peer exclusion, including consideration of personal benefit, harming others’ welfare, personal concern, and punishment. The use of social reasoning strategies was similar across the two groups of students except that Taiwanese students relied more on judgment (i.e., social-moral evaluation of someone’s social conduct) whereas U.S. students generated more alternative hypotheses (i.e., presenting new hypotheses or interpretations about the given issue).